2007
DOI: 10.2119/2007-00046.wang
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Proliferation and Enhancing Chemosensitivity to Taxanes in Osteosarcoma Cells by RNA Interference-Mediated Downregulation of Stathmin Expression

Abstract: Stathmin (Oncoprotein18), a signal transduction regulatory factor, plays an important role in cell division and malignant tumor development. Stathmin is a ubiquitous intracellular phosphoprotein that is overexpressed in a variety of human malignancies, including osteosarcoma. To investigate the potential use of stathmin as a therapeutic target for human osteosarcomas, we employed RNA interference [small interfering RNA (siRNA)] to reduce stathmin expression in human osteosarcoma cell lines and analyzed their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
26
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 27 publications
6
26
0
Order By: Relevance
“…The growing evidence has shown that miR-21 is an oncogenic miRNA and is highly expressed in a variety of malignant tumors (24,25). It is still a challenging question as to how the expression of miRNAs is regulated.…”
Section: Discussionmentioning
confidence: 99%
“…The growing evidence has shown that miR-21 is an oncogenic miRNA and is highly expressed in a variety of malignant tumors (24,25). It is still a challenging question as to how the expression of miRNAs is regulated.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, stathmin was also found to be overexpressed in osteosarcoma and ovarian carcinoma cells, and the overexpression of this gene signiWcantly correlated with prognosis of patients (Zhang et al 2004;Wei et al 2008). Moreover, we found that small interfering RNA (siRNA) or antisense-mediated downregulation of stathmin expression could lead to proliferation inhibition and chemosensitivity enhancement in human osteosarcoma cells (Zhang et al 2006;Wang et al 2007). Therefore, stathmin might be involved in the tumor carcinogenesis, proliferation, metastasis and chemmoresistance, while the high levels of this molecule are signiWcantly correlated with tumor progression and patient outcome (Belletti et al 2008;McGrogan et al 2008) .…”
mentioning
confidence: 82%
“…[33][34][35] Previously, we have described bi-shRNA STMN1 BIV cleavage product detection both in vitro and in vivo, but not in patients. 21 Data presented in this report are the first demonstration that STMN1 expression can be knocked down by RNAi approach in humans.…”
Section: Discussionmentioning
confidence: 99%